Filamentous aggregations of phosphorylated α-synuclein in Schwann cells (Schwann cell cytoplasmic inclusions) in multiple system atrophy - Nakamura, Keiko; Mori, Fumiaki; Kon, Tomoya; Tanji, Kunikazu; Miki, Yasuo; Tomiyama, Masahiko; Kurotaki, Hidekachi; Toyoshima, Yasuko; Kakita, Akiyoshi; Takahashi, Hitoshi; Yamada, Masahito; Wakabayashi, Koichi (Acta neuropathologica communications, 2015)
The histological hallmark of multiple system atrophy (MSA) is the presence of filamentous aggregations of phosphorylated α-synuclein in oligodendrocytes, referred to as glial cytoplasmic inclusions (GCIs). Although GCIs can occur widely in the central nervous system, accumulation of phosphorylated α-synuclein in Schwann cells has not been reported in MSA. We immunohistochemically examined the cranial and spinal nerves, peripheral ganglia and visceral autonomic nervous system of patients with MSA (n = 14) and control subjects (n = 20). In MSA, accumulation of phosphorylated α-synuclein was found in the cytoplasm of Schwann cells. These Schwann cell cytoplasmic inclusions (SCCIs) were also immunopositive for ubiquitin and p62. SCCIs were found in 12 of 14 patients with MSA (85.7 %). They were most frequent in the anterior nerve of the sacral cord and, to a lesser extent, in the cranial nerves (oculomotor, glossopharyngeal-vagus and hypoglossal nerves), and spinal and sympathetic ganglia. SCCIs were rarely found in the visceral organs. Immunoelectron microscopy demonstrated that the SCCIs consisted of abnormal filaments, 15-20 nm in diameter. No such inclusions were found in controls. The present findings indicate that Schwann cells are also involved in the disease process of MSA.